Dinamika Kehidupan Multikultural Di Kampung Kajanan, Buleleng, Bali Dan Potensinya Sebagai Sumber Belajar Sejarah Di SMA: Multikultural - Cala, Maria Ulda; Purnawati, Desak Made Oka; Yasa, I Wayan Putra (Universitas Pendidikan Ganesha, 2024)
This study aims to determine: the growth and development of the dynamics of a multicultural society in Kajanan Village, Singaraja, Bali, the forms of multiculturalism in the community in Kajanan Village, Singaraja, Bali, aspects of multiculturalism that can be utilized as a source of learning history in high school. The research method used is historical research methods with a qualitative approach including: the first is heuristic, namely the process of searching and collecting historical sources, the second is source criticism or verification, namely the stage of testing data sources, the third is interpretation, namely the stage of interpreting data before it can then be written into historical writing and finally historiography, namely the stage of writing history which can be done after the data has been collected through previous processes. The results of the study show that: The growth and development of a multicultural society in Kajanan Village, Singaraja Bali is inseparable from trade, intermarriage, population movements and political policies. From these various activities, many ethnic groups flock to Bali, especially in Buleleng, North Bali. To become a multicultural society in Kajanan Village. The form of community multiculturalism in Kajanan Village can be seen in the social, cultural, economic and building fields. Aspects that can be developed as a source of learning projects to strengthen the profile of Pancasila students are: Aspects of history, aspects of tolerance, social aspects and cultural aspects. Keywords: Multicultural, Kajanan Village, History Learning Resources